Oceanic pCO2 in the Indian sector of the Southern Ocean during the austral summer–winter transition phase. (August 2015) - Shetye, Suhas S.; Mohan, Rahul; Patil, Shramik; Jena, Babula; Chacko, Racheal; George, Jenson V.; Noronha, Sharon; Singh, Neelu; Priya, Lakshmi; Sudhakar, Maruthadu
Abstract: Biogeochemical processes in the Southern Ocean (SO) play a significant role in regulating the global climate. The physical and biological processes controlling p CO2 in the surface mixed layer at the Indian sector of SO were observed, and changes during the transition period from summer to early winter (January, February and March) were compared. An existing, one-dimensional model describing the mixed-layer carbon cycle was used to determine the relative contributions of biological activity, mixing, thermal and air–sea fluxes on p CO2 . A breakdown of the controls shows that the p CO2 distributions are dominated by biological processes during January and February, whereas mixing and thermal effects contributed equally during March. Biological processes accounting for p CO2 decrease reached a maximum value of 108 µatm during January. Our results are categorized according to distinct hydrographic regions such as oceanic fronts Sub-tropical front (STF), Sub-Antarctic front (SAF), Polar front (PF) and Antarctic zone (AZ). p CO2 varied among these three studied months, the mean p CO2 increasing from 286 µatm in January to 337 µatm in March, whereas an opposite trend was observed with dissolved oxygen (O2 ). The satellite-derived Primary Production (PP) decreased from January to March and also from the STF towards the SAF, PF and AZ. The observed differences in PP and p CO2 during the three months showed the total diatom count ranging from 0.49×10 3  cells/l in March to 3.2×10 3  cells/l in January. Our study indicates that the drawdown in sea-surface p CO2 from March to January could be attributed to the light availability, shallow Mixed layer depth (MLD), high PP, nutrient availability, and low upwelling velocity. Eddies play an important role in regulating p CO2 that require further studies to quantify their percentage contribution in p CO2 rise/drawdown.